Pengenalan dan Sosialisasi Penggunaan Aplikasi Statistika untuk Penelitian Tindakan Kelas Bagi Guru-Guru SMA - TIUAJ, yanto; Prasetya, Wibawa (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2023)
The aim of this activity is to provide knowledge about basic statistics and the application of statistical software package for classroom action research. Senior high school teachers from 4 schools participated in this workshop. They were provided with the basic knowledge of statistics, the use of statistics and research methodology for classroom action research and how to apply Minitab to help in data calculation and interpretation. During workshop, the participants were demonstrated the use of Minitab in the laboratory of Statistics and, Industrial Engineering Department, Atma Jaya Catholic University of Indonesia.